A PRINCIPAL COMPONENT ANALYSIS ON ELEMENTS OF THE E-IMAGE MODEL: TOWARDS BETTER LEVERAGING OF INTERNET MARKETING IN GHANA - Frimpong Opuni, Frank; Adu-Gyamfi, Kwame; Opoku, Emmanuel (British Journal of Marketing Studies, 2014)
The purpose of this study was to identify elements of the e-image model that influence Ghanaians to patronise products or services online or that make them yield to online marketing information. In this study, a standard questionnaire was used to collect data from 250 internet market (i.e. e-market) users in Ghana. Principal Component Analysis was used to analyse data. Five components were found to constitute all the elements of the e-image model in a Ghanaian context. The five components retrieved composed of all factors in the e-image model, with a variance of 95% explained. The experience component was merged to the feedback and reputation component, which explained the highest variance of 38.6%. Information content, website characteristics, security and others are the other components in the e-image model that were confirmed in a Ghanaian context without any change